Looking Inside Traditional Islamic Schools: Concerns and Prospects of Learning Culture - Silahuddin, Silahuddin; Saiful, Saiful; Ikhwan, M.; Zulfikar, Teuku; SH, Hendra (Jurnal Ilmiah Peuradeun, 2025)
Dayah is a designation for the traditional Islamic boarding school in Aceh, an institution that plays a crucial role in education, knowledge dissemination, and shaping religious identity in Aceh society. To produce well-rounded graduates, Dayahs must stay abreast of modern developments and cultivate a dynamic, inclusive academic culture. However, Dayahs have struggled to demonstrate such openness, leading to challenges to their relevance. This research employed qualitative methods to investigate the academic culture within the Dayah education system in Aceh, re-evaluate factors influencing its development, and outline future growth prospects. The study focused on three Dayahs: Ruhul Islam, Ruhul Falah, and Darul Maghfirah. The findings revealed that the academic culture in these institutions has been declining due to several factors: reliance on a traditional curriculum and teacher-centered instruction, generational transmission of outdated practices, and lack of contemporary organizational structure. These issues hinder learning, stifling the freedom to voice opinions, knowledge acquisition, and effective management. To improve the academic culture in Dayah, it is recommended to enhance engagement and communication with all stakeholders, implement a structured development plan, and improve the quality of human resources. By addressing these areas, Dayahs can foster a more dynamic and inclusive academic environment.